State Instruments of Protectionism in Russian Industrial Policy: Theory and Practice - A. A. Rashchikov (Управленческое консультирование, 2025)
The article examines the specifics and features of protectionism in Russian modern management. Special attention is paid to the tools with which the authorities manage a complex industrial structure. The emphasis is placed on the fact that industrial policy is the most important direction in terms of strategic objectives and in the long term. The traditional theory of protectionism is used as the theoretical basis of the study. The article highlights the fact that, as in any country, in Russia the viability of the industrial production sector plays a crucial role, and its importance in the growth of national production can hardly be overestimated. The objectives of protectionism in Russian industry, which are important for the protection of domestic production, as well as GDP growth, are considered. In addition, the instruments of protectionism stimulate the ability to protect the industrial sector from external factors, thereby reducing the consequences. The concept of protectionism in theoretical discourse is defined from different points of view. But the main point of contact in various definitions is the definition of protectionism as a whole state policy, both in theory and in practice, which restricts imports from other countries by applying international sanctions using various methods. Such methods include import restrictions, quotas and others with the main purpose of protecting local industry by restricting the sale of foreign goods on the market. The purpose of the article is to identify the main methods of state regulation in the industrial sector from the point of view of protectionism tools. The subject of the study is the theoretical and practical foundations of protectionist policy in modern Russia. The methods that were applied in the work will include a theoretical overview, a method of analysis, deduction, generalization. The result of the work are generalizing conclusions describing the most effective ways and directions of Russia’s industrial policy in the context of protectionism, comparing their theoretical foundations with practical application. The article considers several cases that help to identify the problems of modern industrial management policy. Among such obvious problems, it is worth highlighting the insufficient level of orientation to the new driving forces of technological change, the presence of a high degree of separation of the political landscape, and the low level of selection of successful practices.